Effect of different carbon sources on Δ5 desaturation activity of HTC cells - Tacconi de Alaniz, María Josefa (1982)
The effect of different carbon sources on Δ5 desaturation activity in Minimal Deviation Hepatoma 7288 c (HTC) cells was studied. When HTC cells were incubated in the absence of carbon sources in the medium (fasted cells) the conversion of [1-14C]eicosa-8,11,14-trienoic acid to arachidonic acid increased significantly compared to those cells incubated in S-77 medium (fed cells). This activity was not modified if fasted. cells were refed with glucose. However, the activity decreased significantly by the addition of lactalbumin hydrolysate to fasted cells. This effect can not be attributed to individual aminoacids since the addition of them to an aminoacid free medium produced no changes on Δ5 desaturation activity. The incubation of HTC cells with S-77 medium supplemented with glucose, pyruvate or glucose plus pyruvate, showed similar Δ5 desaturation activity to those cells incubated in S-77 medium alone.